Mekanisme transmisi energi dalam prespektif ekonomi terhadap emisi karbon di Indonesia - Priyagus Priyagus (FORUM EKONOMI, 2023)
This study aims to investigate the mechanism of energy transmission in an economic perspective on the formation of carbon emissions in Indonesia, both in the short and long term. The analytical method uses dynamic 2SLS with data from 1990-2014. The estimation results explain that energy consumption has a significant and positive effect in the short and long term on economic growth, then economic growth has a significant and positive effect on carbon emissions. In other words, there is a real and positive transmission of energy in the formation of carbon emissions. The government's commitment to law enforcement and bureaucracy that are conducive to reducing emissions has not yet yielded optimal results. Energy-saving behavior, increased green investment for (EBT) and broad community involvement, can be an alternative to reduce carbon emissions in Indonesia